Platelets modulate endothelial cell response to dynamic shear stress through PECAM-1. Issue 150 (February 2017) - Meza, Daphne; Shanmugavelayudam, Saravan K.; Mendoza, Arielys; Sanchez, Coralys; Rubenstein, David A.; Yin, Wei
Abstract: Introduction: Both vascular endothelial cells and platelets are sensitive to blood flow induced shear stress. We have recently reported that platelet-endothelial cell interaction could greatly affect platelet activation under flow. In the present study, we aimed to investigate how platelet-endothelial cell interaction affected endothelial cell inflammatory responses under flow. Materials and methods: Human coronary artery endothelial cells were exposed to normal or low pulsatile shear stress with or without the presence of platelets. Following shear exposure, endothelial cell ICAM-1 expression was measured using ELISA, Western blot and PCR; cell surface PECAM-1 expression/phosphorylation was measured using ELISA. Platelet adhesion to endothelial cells was quantified using immunofluorescence microscopy. To determine the role of PECAM-1 in platelet-endothelial cell interaction, endothelial cell PECAM-1 expression was suppressed using siRNA. Results: Pathological low shear stress induced a significant increase in endothelial cell ICAM-1 expression, at both protein and mRNA levels. Platelet adhesion to endothelial cells increased significantly under low shear stress, co-localizing with PECAM-1 at endothelial cell junctions. The presence of platelets inhibited low shear stress-induced ICAM-1 upregulation. When endothelial cell PECAM-1 expression was suppressed, platelet adhesion to endothelial cells under low shear stress decreased significantly; endothelial cell ICAM-1 expression was not affected by shear stress, with or without platelets. Conclusions: These results suggested that PECAM-1 could mediate platelet adhesion to endothelial cells under shear stress. Platelets binding to endothelial cells interfered with endothelial cell mechanotransduction through PECAM-1, affecting endothelial cell inflammatory responses towards pathological shear flow. Highlights: Endothelial cells respond to pathological shear stress by PECAM-1 phosphorylation. Platelets can adhere to endothelial cells through PECAM-1 under shear stress. Platelets can affect endothelial cell inflammatory response to shear stress, potentially through PECAM-1.